On a MIMO-based open wireless architecture space-time complementary coding. - Hsiao-Hwa Chen (IEEE Communications magazine)
This article proposes a MIMO-based open wireless architecture for next-generation wireless systems. The use of space-time complementary coding in the proposed OWA scheme contributes to a great improvement in system performance due to the joint spatial diversity and multiplexing advantages achieved by the STCC-MIMO scheme. The proposed STCC-MIMO-based OWA scheme offers an unified platform that integrates various attractive features, such as link adaptation, spatial diversity and multiplexing trade-off, and accurate channel estimation. The application of innovative pair-wise complementary codes and offset stacking spread spectrum in the STCC-MIMO scheme helps to boost the overall spectral efficiency due to its near interference-free operation. MIMO systems play an extremely important role in 4G wireless, and therefore it is desirable that the OWA support different MIMO configurations. This article shows that the proposed STCC-MIMO scheme offers great flexibility to implement a MIMO system suitable for different diversity and multiplexing requirements.